Superposition principle of impact on the working environment of actuating elements for site preparation machines - Prystailo, M.; Balaka, M.; Mozharivskyi, V.; Drachuk, V.; Honta, I.; Пристайло, Микола Олексійович; Балака, Максим Миколайович; Можарівський, Валентин Петрович; Драчук, Володимир Володимирович; Гонта, Ігор Петрович (Харківський національний автомобільно-дорожній університет, 2024)
The article proposes the superposition principle of the influence of several factors on the working environment at the same time, such as static and dynamic load, thanks to the accumulation of energy to create a high-speed force pulse on the cutting edge with the aim of pre-forming a com pressed zone in the array, which will reduce the energy intensity of the process.
Принцип суперпозиції впливу на робоче середовище виконавчих елементів машин для підготовчих робіт
Keywords: ripper-pick; soil destruction; power intensity reduction; tip with the dynamic cutting edge; superposition principle; розпушувач-кайлувальник; руйну вання ґрунту; зменшення енергоємності; наконе чник з динамічною різальною кромкою; принцип суперпозицій; 621.878.23; 10.30977/BUL.2219-5548.2024.105.0.61